A novel supramolecular polymer gel constructed by crosslinking pillar[5]arene-based supramolecular polymers through metal–ligand interactions. Issue 98 (15th October 2015) - Wang, Pi; Xing, Hao; Xia, Danyu; Ji, Xiaofan
Abstract : A novel heteroditopic A–B monomer was synthesized and used to construct linear supramolecular polymers utilizing pillar[5]arene-based host–guest interactions. Upon addition of Cu 2+ ions, a supramolecular polymer gel formed through metal–ligand interactions. Abstract : A novel heteroditopic A–B monomer was synthesized and used to construct linear supramolecular polymers utilizing pillar[5]arene-based host–guest interactions. Specifically, upon addition of Cu 2+ ions, the supramolecular polymer chains are crosslinked through metal–ligand interactions, resulting in the formation of a supramolecular polymer gel. Interestingly, this self-organized supramolecular polymer can be used as a novel fluorescent sensor for detecting Cu 2+ ions.